ANALISA TINGKAT PENCEMARAN LOGAM BERAT TIMBAL (PB) DI DAERAH ALIRAN SUNGAI DELI SUMATERA UTARA - Afrianti, Suratni; Irni, Julaili (BIOLINK : Jurnal Biologi Lingkungan Industri Kesehatan, 2020)
The Deli river is the Pioritas I River Basin in North Sumatra, the level of community activity in the Deli river border is high such as settlements, offices, schools and industries, the community has the potential to produce a lot of solid waste in the estuary to the river body so as to make the river polluted, parameters pollution is heavy metal. The purpose of this study is to analyze the Pb content in the Deli River using the AAS tool, from the analysis of the deli river pollution level, the Lead Analysis Result (Pb) obtained from upstream to downstream is an average value of 0.003 ppm, this means that lead pollution (Pb) in the river Deli is still relatively low or has not been polluted by lead heavy metals (Pb) because according to Government Regulation No. 82 of 2001 concerning Water Quality Management and quality pollution control of 0.03 ppm standard water.